Peran Satuan Polisi Pamong Praja dalam Penertiban Pengemis di Kota Padang - Revi Oktafiola; Lince Magriasti (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2023)
This research purpose to reveal the role of the Civil Service Police Unit in controlling beggars. This study uses quasi-qualitative methods and determines research informants using purposive sampling. This research uses techniques by source triangulation and techniques by data collection using observation, interviews and documentation. While the techniques for data analysis used by researchers are data collection, data reduction, display and verification and confirmation of conclusions. The research results shown that the Civil Service Police Unit in controlling beggars in the city of Padang has carried out its duties as a regulator, dynamist, facilitator and catalyst well. However, in the implementation of controlling beggars there are internal and external constraints. To overcome these obstacles with the entire community and the government in dealing with beggars in the city of Padang